Macular pigment optical density measured by heterochromatic modulation photometry - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Lüssen, Ulrich-Christoph; Berendschot, Tos T. J. M.; Pokorny, Joel; Kremers, Jan (PLoS ONE, 2014)
To psychophysically determine macular pigment optical density (MPOD) employing the heterochromatic modulation photometry (HMP) paradigm by estimating 460 nm absorption at central and peripheral retinal locations.For the HMP measurements, two lights (B: 460 nm and R: 660 nm) were presented in a test field and were modulated in counterphase at medium or high frequencies. The contrasts of the two lights were varied in tandem to determine flicker detection thresholds. Detection thresholds were measured for different R:B modulation ratios. The modulation ratio with minimal sensitivity (maximal threshold) is the point of equiluminance. Measurements were performed in 25 normal subjects (11 male, 14 female; age: 30±11 years, mean ± sd) using an eight channel LED stimulator with Maxwellian view optics. The results were compared with those from two published techniques - one based on heterochromatic flicker photometry (Macular Densitometer) and the other on fundus reflectometry (MPR).We were able to estimate MPOD with HMP using a modified theoretical model that was fitted to the HMP data. The resultant MPODHMP values correlated significantly with the MPODMPR values and with the MPODHFP values obtained at 0.25° and 0.5° retinal eccentricity.HMP is a flicker-based method with measurements taken at a constant mean chromaticity and luminance. The data can be well fit by a model that allows all data points to contribute to the photometric equality estimate. Therefore, we think that HMP may be a useful method for MPOD measurements, in basic and clinical vision experiments.
EVALuna2:21179